First Detection and Characterization of Streptococcus dentapri from Caries Active Subject - Salman, Hamzah Abdulrahman (J Clin Diagn Res, 2017)
INTRODUCTION: Mutans streptococci (MS) are a group of oral bacteria generally regarded as the principal agents in the pathogenesis of dental caries. AIM: The study aimed was characterize S. dentapri based on phylogenetic analysis and phenotypic methods from Caries Active Subject. MATERIALS AND METHODS: While sequencing MS species which were isolated from 65 caries active subjects, one strain of S. dentapri was detected. Dental plaque samples were processed and cultured on mitis salivarius bacitracin agar. S. dentapri was characterized using phylogenetic analysis, colony morphology characterization and biotyping. RESULTS: Among the study population, one strain designated as H14 was identified as S. dentapri by 16S rDNA sequencing. Morphologically, S. dentapri could not differentiate from other species of MS. S. dentapri H14 demonstrated biotype II biochemical characteristics of MS. The phylogenetic analysis showed S. dentapri is closely related to S. macacae. CONCLUSION: The study concludes that S. dentapri can inhabit the human oral cavity and therefore further investigations are warranted to determine its role in caries.